The Impact of the Project-Based Learning Model on Enhancing Students' Civic Skills in Maintaining National Diversity through Digital Literacy in Eighth Grade at SMP Negeri 2 - Alfina Putri Wijayanti; Wildan Nurul Fajar; Elly Hasan Sadeli (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine whether the project-based learning model affects improving students' civic skills concerning the maintenance of national diversity through digital literacy among eighth-grade students at SMP Negeri 2 Tonjong. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of eighth graders A as the control group (n=32) and eighth graders B as the experimental group (n=32). Data collection techniques included surveys/questionnaires, tests, and documentation, analyzed using paired sample tests and independent sample t-tests, with a result of 0.000, which is less than 0.05, indicating a significant effect of the project-based learning model on enhancing students' civic skills regarding the maintenance of national diversity through digital literacy. This is evidenced by the difference between the experimental and control groups, with the experimental group demonstrating 94% intellectual skills and 82% participatory skills, compared to 70% and 68.7%, respectively, in the control group. These results suggest that the project-based learning model is effective in improving students' civic skills in this context.